2017
DOI: 10.1186/s12885-017-3323-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical benefit of adding oxaliplatin to standard neoadjuvant chemoradiotherapy in locally advanced rectal cancer: a meta-analysis

Abstract: BackgroundNeoadjuvant fluoropirimidine (5FU)-based chemoradiotherapy (CRT) has been considered the standard of care for locally advanced rectal cancer (LARC). Whether addition of oxaliplatin (OXP) will further improve clinical outcomes is still debated. We conducted a meta-analysis to evaluate the role of OXP in this patient population.MethodsLiterature searches were carried out in PubMed, Medline and Scopus databases. End points were overall survival (OS), disease free survival (DFS), local failure (LF) and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 19 publications
(9 reference statements)
5
34
1
1
Order By: Relevance
“…Two meta-analyses concluded decreased risk for DM but without any improvement of DFS or OS. 137,138 Short course radiotherapy…”
Section: Radiotherapymentioning
confidence: 99%
“…Two meta-analyses concluded decreased risk for DM but without any improvement of DFS or OS. 137,138 Short course radiotherapy…”
Section: Radiotherapymentioning
confidence: 99%
“…A recent meta-analysis suggested a significant clinical benefit in terms of distant failure by adding oxaliplatin to the standard fluoropyrimidine-based CRT. 4 However, among the trials included, it was not possible to extrapolate patient age details; thus, a subsequent subset analysis was not performed. Definitive conclusions are still pending, and further clinical data are paramount to better clarify the precise role of the intensified neoadjuvant approach, especially for elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…There have now been seven major trials on oxaliplatin [ 17 – 23 ] and two of those demonstrated a benefit for oxaliplatin regarding DFS [ 20 , 23 ]. Meta-analyses have also demonstrated this benefit [ 24 , 25 ]. In patients receiving neoadjuvant treatment, CRM positivity is one of the strongest predictive factors of local recurrence [ 26 ].…”
Section: Discussionmentioning
confidence: 99%